Effect of Splinting of Tilted External Hexagon Implants on 3-Unit Implant-Supported Prostheses in the Posterior Maxilla: A 3D Finite Element Analysis - de Faria Almeida, Daniel A.; Verri, Fellippo R. [UNESP]; Lemos, Cleidiel A. A.; de Souza Batista, Victor E.; Santiago Júnior, Joel. F.; Rosa, Cleber D. D. R. D. [UNESP]; Noritomi, Pedro Y.; Pellizzer, Eduardo P. [UNESP] (Wiley, 2021)
Purpose: To assess the effects of tilted external hexagon implants and splinted restorations in terms of stress distribution on the bone tissue, implants, and prosthetic screws, using three-dimensional finite element analysis. Materials and Methods: Six models were used to simulate a posterior maxilla bone block (type IV) from the first premolar to the first molar. Each model included three 4.1-mm-diameter external hexagon implants with varying inclinations (0°, 17°, and 30°) and crown designs (splinted and nonsplinted restorations). The forces applied were as follows: 400 N axially (50 N for each slope of the cusp) and 200 N obliquely (45° only on the buccal slope of the cusp). Stress distribution on the implants and prosthetic screw was evaluated using Von Mises stress, while the maximum principal stress was used to evaluate the stress distribution in the bone tissue. Results: The oblique load increased the stress on all the structures in all the models. Increased inclination of the implants resulted in higher stress concentration in the bone tissue, implants, and prosthetic screws. However, splinted restorations contributed to reduction of the stress for the oblique loading, mainly in the bone tissue and prosthetic screw of the first molar, as the stress was shared between the first and second premolar restorations. Conclusions: Tilted implants increased proportionally the stress on bone tissue and prosthetic screws of models. Additionally, splinting restorations reduced the stress concentration area in the simulated bone tissue, implants, and prosthetic screws in the first molar, as the stress was shared with the adjacent implants.